Electrochemical oxidation of 2,5-dimercapto-1,3,4-thiadiazole on carbon electrodes modified with Ru(III) Schiff base complex - Pazalja, Mirha (Array, 2021)
The thiol compound 2,5-dimercapto-1,3,4-thiadiazole is a potential cathode material. The redox reactions of the mentioned thiol compound are slow at room temperature but can be enhanced using electron transfer mediators. The electrochemical oxidation of 2,5-dimercapto-1,3,4-thiadiazole on the surface of carbon electrodes modified with Ruthenium(III) Schiff base complex was studied by voltammetric methods and amperometric flow injection analysis. The electrocatalytic properties of Ruthenium(III) Schiff base complex on glassy carbon and screen printed carbon electrodes are enhanced by the addition of multi-walled carbon nanotubes and Nafion. Voltammetric studies showed that anodic oxidation of DMcT on a modified glassy carbon electrode occurs at a potential of +0.28 V vs. Ag/AgCl in Britton-Robinson buffer (pH 6.50). Flow injection amperometric measurements were performed at +0.20 V vs. Ag/AgCl in Britton-Robinson buffer solutions pH 6.50 at a 0.40 cm3 min–1 flow rate. The results of amperometric measurements for modified screen printed and glassy carbon electrodes showed that the screen printed electrode had a lower value of detection limit (0.38 mg dm–3) and quantification (1.28 mg dm–3), and a linear dynamic range from 1 to 500 mg dm–3 of 2,5-dimercapto-1,3,4-thiadiazole. Modified glassy carbon electrode provided a linear dynamic range up to 750 mg dm–3 of 2,5-dimercapto-1,3,4-thiadiazole with a detection limit of 3.90 mg dm–3 and quantification of 13.20 mg dm–3.